In Vitro Biofilm Formation on Aryl Ketone Polymer (AKP), A New Denture Material, Compared with That on Three Traditional Dental Denture Materials - Cadie Martin; Laura Purevdorj-Gage; Wei Li; Timothy J. Shary; Bin Yang; Ryan J. Murphy; Christine D. Wu (International Journal of Dentistry)
Control of denture plaque biofilms is a practical approach to preventing persistent oral infections such as denture stomatitis. Objectives. This study compared in vitro biofilm attachment and growth on a new denture material, Ultaire® AKP, with that on traditional denture materials including cobalt chrome (CoCr), polymethyl methacrylate (PMMA), and polyoxymethylene (POM). Methods. Microbial biofilms were grown with cultures of Candida albicans, Streptococcus mutans UA159, or a mixed Streptococcus spp. (S. mutans 700610/Streptococcus sanguinis BAA-1455) for 6 hours in a static protocol or 24 hours in a dynamic protocol for each material. Adherent biofilm cells were removed, and viable colony-forming units (CFUs) were enumerated. Confocal microscopy of the 24-hour Streptococcus spp. biofilms was used to determine biofilm mass and roughness coefficients. Results. The rank order of C. albicans attachment after 6 hours was CoCr > PMMA∗ > Ultaire® AKP∗ (∗vs CoCr, p≤0.05), and that for 24-hour biofilm growth was CoCr > Ultaire® AKP∗ > PMMA∗ (∗vs CoCr, p≤0.05). The rank order of S. mutans biofilm attachment was CoCr > POM > Ultaire® AKP∗ > PMMA∗ (∗vs CoCr, p≤0.05), and that for the 24-hour Streptococcus spp. biofilm growth was POM > Ultaire® AKP > PMMA > CoCr∗ (∗vs POM, p≤0.05). Confocal images revealed structural differences in Streptococcus spp. biofilms on CoCr compared with the other test materials. Significantly lower roughness coefficients of Streptococcus spp. biofilms on Ultaire® AKP were noted, suggesting that these biofilms were less differentiated. Ultaire® AKP promoted significantly less C. albicans and S. mutans biofilm attachment than CoCr at 6 hours and C. albicans growth at 24 hours. Streptococcus spp. biofilms on Ultaire® AKP were less differentiated than those on other test materials. Conclusion. In addition to its material strength, Ultaire® AKP represents an attractive option for denture material in removable partial dentures.